ANALISIS AKURASI DAN KARAKTERISTIK TERJEMAHAN AL-QUR`AN DAN TERJEMAHNYA BAHASA JAWA BANYUMASAN - Nurul Husna (AL ITQAN: Jurnal Studi Al-Qur'an, 2020)
Al-Qur`an dan Terjemahnya Bahasa Jawa Banyumasan is a manifestation of the need for the contribution of the Quran to local communities, especially Banyumasan. This translation was compiled by a team of translators who were delegated by the Ministry of Religious Affairs of the Republic of Indonesia in 2011. The use of Banyumasan Javanese as an object language for translation is a fresh thing. This research is crucial as it is the first study of the Banyumasan translation of the Quran. This study aims to understand the methods of translation and also to look at the accuracy of the translation. This research is a library research using descriptive-analysis method. The references used in analyzing the accuracy of this translation are the Banyumasan dialect dictionary and linguists' statements obtained from the author's interviews. The results of this study indicate that this translation uses a contextual method with several improvisations to explain the meaning, loanwords from both Indonesian and Arabic, hierarchical language, affirmation of meaning, and also distortion of meaning that does not change the meaning of the verse. Keywords: Quran Translation, Banyumasan Javanese Language, dialect, accuration